Radziecki przewodnik turystyczny po Moskwie: retrospektywa - Olena Kowalenko (Z Badań nad Książką i Księgozbiorami Historycznymi, 2017)
The article gives a brief description of Moscow guide books printed between 1922 and 1991. The retrospective of Soviet texts is preceded by tracing the origins of Moscow travel guides, which goes back to travel notes from the 16th and 17th centuries. The paper presents 34 Soviet itineraries by providing their composition and content summary. Also, it demonstrates and explains the referential and syncretic patterns of Soviet guidebooks, and the shift made at the turn of the NEP era and the 1930s. Tourism evolution, city planning and state censorship are discussed among the factors that influence travel itineraries. The diachronic approach allows to note continuity and transformation elements of Soviet travel guides to Moscow.